Koli representation outside Mazagaon Koliwada - Mumbai Archive Project Team (Jio Institute, 2024)
Among the first people to live in the Bombay Islands were the Kolis. Aside from Kolis, the area was populated by groups of people who worked in occupations that supported the regional economy. These included the Agris and Kunbis (paddy growers), the Bhandaris (toddy tappers), and the Mitha Agris (saltpan workers). However, as times changed, only the Kolis continued to engage in their traditional profession and have maintained a distinct cultural identity.